1994
DOI: 10.1007/bf02422959
|View full text |Cite
|
Sign up to set email alerts
|

Inherently safe lead — bismuth — cooled reactors

Abstract: The strategic path toward the safest possible nuclear power plants is to switch to inherently safe nuclear reactors, capable of self-shielding, without interference by man, in any accident situations. Examples of such plants are modular medium and low-power plants based on fast reactors with a breeding ratio close to one. As a result, in such plants the operational reactivity margin is less than/~eff, negative temperature feedbacks are present, the void effect of reactivity is negative, and the colloant is a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…18,19 A methodology for injection of gaseous mixtures of H 2 and H 2 O into the coolant flow to purify the Pb and Pb-Bi circuits of slag deposits. 20 The development of solid phase oxidizers to control the thermodynamic activity of Pb and Pb-Bi coolants. 20 The development of an absorption technique to extract dissolved impurities in liquid-metal coolants (e.g., Ga, Pb, Pb-Bi).…”
Section: Salient Results Of Their Research Are As Followsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 A methodology for injection of gaseous mixtures of H 2 and H 2 O into the coolant flow to purify the Pb and Pb-Bi circuits of slag deposits. 20 The development of solid phase oxidizers to control the thermodynamic activity of Pb and Pb-Bi coolants. 20 The development of an absorption technique to extract dissolved impurities in liquid-metal coolants (e.g., Ga, Pb, Pb-Bi).…”
Section: Salient Results Of Their Research Are As Followsmentioning
confidence: 99%
“…20 The development of solid phase oxidizers to control the thermodynamic activity of Pb and Pb-Bi coolants. 20 The development of an absorption technique to extract dissolved impurities in liquid-metal coolants (e.g., Ga, Pb, Pb-Bi). The technique is based on retention of dissolved and highly dispersed impurities in a liquid-metal by absorbent surfaces in a filter medium, through which the coolant is pumped.…”
Section: Salient Results Of Their Research Are As Followsmentioning
confidence: 99%
“…8, AUGUST 2003 the colder regions of the system. The Russians 6) have found that steels with relatively low concentrations of nickel (0.8%) and relatively high concentrations of silicon (1.3%) and vanadium (0.4%) seem resistant to corrosion when in contact with molten Pb-alloys at temperatures up to 600 • C. 5,79,80) Corrosion rates of steel by Pb-alloys have been reduced through the addition of oxidation inhibitors (e.g., zirconium, tungsten, and chromium) in the coolant 66,77,78) and surface coatings. Inhibitors require strict concentration control, as depletion of these minor additives adversely affects the corrosion rate.…”
Section: Compatibility Of Molten Lead Alloy With Fuel Cladding Amentioning
confidence: 99%
“…Polonium-210 is very toxic and difficult to contain [7]. Nonetheless, the former Soviet Union developed and used PbBi-cooled reactors, and the PbBi-cooled approach has been proposed by several laboratories as an advanced power production reactor [17][18][19][20]. Bismuth possesses a higher melt temperature than the PbBi eutectic and offers no significant advantages over PbBi-cooled reactors.…”
Section: Heavy-metal Coolantsmentioning
confidence: 99%